Computational Analysis of the Functional and Structural Impact of SNPs Present in Genes of the Mitochondrial Biogenesis Pathway - Ribeiro, Michelly Ferreira; Alencar, Sérgio Amorim de (Research Aspects in Biological Science Vol. 9, 2022)
SNPs are punctual mutations that can lead to amino acid changes in proteins and therefore affect their function. Available algorithms in the internet can be used to evaluate the functional and structural impact of these variations. The present work utilized three of these tools, SIFT, PolyPhen and EFIN, with different approaches, such as alignment with homologous sequences, analysis of the structural characteristics and analysis of random forests methods. All the 232 SNPs found in the dbSNP were analysed, related to the PGC-1\(α\), NRF-1, NRF-2, PPAR\(α\), ERR\(α\) e MEF-2 genes, the main regulators of mitochondrial biogenesis pathway, with the intention of verifying which nsSNPs could be considered damaging. This analysis resulted in a group of 40 nsSNPs probably damaging consensus, therefore, predicted as damaging for the three tools. These SNPs were also analyzed by a molecular modeling tool to estimate their effects in the interactions for protein energetic stability. Our results aided in the definition of deleterious nsSNPs present in genes coding proteins involved in the mitochondrial biogenesis and, therefore, predicted to potentially disturb the homeostasis of this metabolic pathway, which is of maximum importance to the maintenance of the corporal energy, lipid levels, as well as other vital biochemical processes to the maintenance of life. The SNPs were also compared to OMIM, and only four presented some association with disease. Besides, among the analyzed variants determined as probably damaging, some characteristics were verified for the suggestion of suitable candidates for future molecular dynamics studies.